Muslimah Fashion Trends and Celebrity Endorsers: An Analysis of Their Influence on the Consumptive Behavior of IAIN Parepare Students on Instagram Social Media. - Arwin, Arwin; Sutrisno, Sutrisno; Hamka, Rezky Amalia; Suherli, Suherli (Peneliti.net, 2025)
This study aims to analyze the influence of Muslim fashion trends and celebrity endorsers on Instagram social media on the consumptive behavior of IAIN Parepare students. The research uses quantitative methods and associative approaches, this study involves collecting data through questionnaires distributed to female students.The population in this study is unknown so that the sample in the study is as many as 100 respondents obtained using the Lemeshow formula. This study uses a multiple linear regression analysis model using the SPSS 25.0 for windows program. The results of the analysis show that Muslim women's fashion trends have a significant influence on consumptive behavior, with a significance value of 0.003, which means less than 0.05. from marketing on social media. In addition, celebrity endorsers also have a significant effect with a significance value of 0.000. Simultaneous tests showed that the two variables together had a significant effect on the consumptive behavior of female students, with an F value of 48.369 which was much larger than the F value of 2.699 in the table. These findings indicate that the influence of social media in the form of fashion trends and endorsements by celebrities can encourage consumptive behavior among female students, potentially influencing their purchasing decisions. This research is expected to provide insight for stakeholders in understanding the dynamics of student consumptive behavior and the implications of marketing on social media.